Sevoflurane Ameliorates Myocardial Cell Injury by Inducing Autophagy via the Deacetylation of LC3 by SIRT1 - Lihua Fan; Deyuan Chen; Jianping Wang; Yini Wu; Dongli Li; Xiaoyan Yu (Analytical Cellular Pathology)
Misfolded and aberrant proteins have been found to be associated with myocardial cell injury. Thus, increased clearance of misfolded or aggregated proteins via autophagy might be a potential option in preventing myocardial cell injury. Sevoflurane may ameliorate myocardial cell injury by affecting sirtuin 1- (SIRT1-) mediated autophagy. Rat models with myocardial cell injury were induced by limb ischemia reperfusion. The model rats received different treatments: sevoflurane, nicotinamide, and autophagy inhibitor 3-methyladenine (3-MA). Autophagy was observed by SEM. The levels of SIRT1 and microtubule-associated protein 1A/1B-light chain 3 (LC3) were measured. Present findings demonstrated that limb ischemia reperfusion induced autophagy. Sevoflurane increased the level of SIRT1, which deacetylated LC3 and further increased autophagic rates. On the other hand, the autophagy was inhibited by sevoflurane and or the inhibitors of SIRT1 and LC3. Present results demonstrated a novel molecular mechanism by which sevoflurane induced autophagy by increasing the level of SIRT1 and reducing the acetylation of LC3.